1983
DOI: 10.1002/1097-0142(19830915)52:6<1044::aid-cncr2820520620>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

A histopathologic study of benign and malignant lymphoepithelial lesions of the parotid gland

Abstract: Twenty‐three cases of benign and malignant lymphoepithelial lesions without Sjögren's syndrome were examined: 21 were classical benign lymphoepithelial lesions, and were mostly found in males older than 50 years of age. The other two cases were identified as undifferentiated carcinoma arising from benign lymphoepithelial lesion (8.7%; 2/23). Histologically, this carcinoma is characterized by the formation of cell nests of variable size and by marked lymphoplasmacytic infiltrations into the stromal tissue. In i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A stromal desmoplastic reaction may be focally noted, but is not usually a prominent finding. Tumor cell spindling may be prominent, and when present brings to mind basal cell adenoma/adenocarcinoma and myoepithelial carcinoma [5,8,31,47,48]. However, none of these other tumors are reactive with nuclear EBER by ISH [8,9,25,28,47].…”
Section: Discussionmentioning
confidence: 99%
“…A stromal desmoplastic reaction may be focally noted, but is not usually a prominent finding. Tumor cell spindling may be prominent, and when present brings to mind basal cell adenoma/adenocarcinoma and myoepithelial carcinoma [5,8,31,47,48]. However, none of these other tumors are reactive with nuclear EBER by ISH [8,9,25,28,47].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have demonstrated the occurrence of myoepithelial islands in biopsy specimens of the parotid glands that also contained lymphoma; therefore, the occurrence of myoepithelial islands can no longer be taken as definitive evidence for the "benign" condition of a biopsy sample (57)(58)(59). Persistent major salivary gland swelling also may result from adenoma or carcinomas (Table 2).…”
Section: Differential Diagnosis Of Enlarged Major Salivary Glandsmentioning
confidence: 99%
“…Although the histologic appearance of these lesions is similar to that found in SS patients, these individuals lack clinical features of oral and/or ocular dryness. Batsakis (12) and Nagao et a1 (57) have suggested that these lesions be termed "benign lymphoepithelial lesions," to contrast these patients with SS patients, in whom KCS and other systemic autoimmune characteristics are present. Finally, metabolic disorders, including alcoholism, malnutrition, pancreatitis, and ingestion of particular foods (12,3 I), might also lead to chronic major salivary gland swelling due to hypertrophy of ductal/acinar elements (31).…”
Section: Differential Diagnosis Of Enlarged Major Salivary Glandsmentioning
confidence: 99%
“…The benign lymphoepithelial lesion (BLL) coined by GODWIN (1) is a histopathologic entity characterized by atrophy of salivary gland parenchyma and lymphocytic infiltration with islands of epithelial and myoepithelial cells (epimyoepithelial islands) replacing the intralobular ducts (2). This lesion is found mostly in association with Sjogren's syndrome (SS), however, occasionally seen as a localized salivary gland lesion in patients who do not have an autoimmune disease (3,4),…”
mentioning
confidence: 99%